Key activities of menu management and analysis performed by SME restaurants in Malaysia - Lai, Jack Hao Bin; Zainal Abidin, Muhammad Rezza; Hasni, Muhamad Zulfikri; Ab Karim, Muhammad Shahrim; Che Ishak, Farah Adibah (Human Resource Management Academic Research Society, 2021)
Menu management and analysis is commonly performed by food and beverage establishments to develop, monitor, and modify menu items. However, previous studies seldom associate and study menu management functions concurrently. These functions include but are not limited to menu planning, menu design, menu pricing, menu operation and menu analysis. This exploratory study explored the measures taken by SME restaurant decision-makers in managing their menus. Participants put forward that the measures taken to manage their menus within their establishments are limited by their capabilities and conditions. Participants identified key activities of menu management and analysis as menu development and modification, menu positioning, menu operational efficiency as well as menu pricing and cost control. At the same time, findings showed that key considerations should be given to employees, customers, restaurant resources and the business environment when making decisions pertaining to menu management and analysis. Practitioners in Kuala Lumpur commonly operate their restaurants without specific menu management method, but manages their respective menus depending on the business environment, resources, and capabilities. Furthermore, practitioners seek operational examples and take pricing references from other successful competitors. This study presents that a balance of both quantitative analytics and qualitative reasoning are key to achieving menu profitability.